Research in arts: a conceptual discussion (Revista da Tulha, 2020)
In summary, this dossier presents, transcribed and edited, the fruitful dialogue that has developed between the round table and the public regarding research in the arts. The entire event is available on the YouTube Platform*. These speeches, recorded and transcribed, went through editing and revision until their final configuration, expressed in this document, in a more concise and formal character. Still in relation to its editing process, thanks to Daniel Portioli Rolnik, Technician for Administrative Affairs of the Music Department of FFCLRP-USP, for the excellent transcription that enabled the organizer to present this final text.https://www.youtube.com/watch?v=4UyqFi-UnlU&t=19028s&ab_channel=USPFILARM%C3%94NICARubensRussomannoRicciardi